Educator and Education Recruitment Strategies and Their Implications on Graduate Quality: A Qualitative Case Study at SDIT Al Malik Prabumulih - Lasni Sutri; Sepriyansyah; Erly Zahara; Nur Indah Hidayati; Kasinyo Harto; Febriyanti (The Future of Education Journal, 2026)
The improvement of the quality of graduates in integrated Islamic elementary schools is highly determined by the quality of educators andeducation staff. Problems that often arise in the management of private schools are the recruitment and selection process that is not fully based onstrategic needs and expected quality indicators of graduates. This study aims to analyze the recruitment and selection strategies of educators andeducation personnel and their implications on the quality of graduates at SDIT Al Malik Prabumulih. The research uses a qualitative approachwith a case study design. Data was obtained through in-depth interviews with school principals, selection teams, and teachers, observation of the recruitment process, and analysis of internal policy documents. The results of the study show that the recruitment strategy based on four teachercompetencies (pedagogic, professional, social, and personality) strengthened with religious standards typical of integrated Islamic schools hassignificant implications for improving the quality of graduates, both in academic aspects and Islamic character. Selection is carried out throughmultiple stages: administration, written and psychological tests, microteaching, Qur'an reading and memorization tests, aptitude tests, and Islamicvalue interviews. Final decision-making is carried out through committee assessments, school principals' istikharah and foundation meetings.Teacher performance evaluations are carried out monthly, semi-annually, and annually with a reward and punishment system. The contribution ofthis research is the development of a model of "Quality-Based Recruitment of Islamic Graduates" that integrates professional competence, valuesuitability, and a continuous evaluation system as a strategy to improve the quality of integrated Islamic elementary schools.